Коефіцієнт пульсацій деяких світлодіодних ламп, наявних на ринку освітлювальних приладів - Падалко, Є. О. (My University, 2021)
The article offers the basic review of the safety requirements that are imposed on LED lamps radiation and represents the main points about the way the LED lamp ripple factor influences the health and well-being of people exposed to the emitted radiation flux. The total number of four different lamps has been studied to determine their ripple ratios. Obtained results show the variance of the ripple ratios and its dependence on the quality of the power module.
Keywords: Коефіцієнт пульсацій; освітлювальний прилад